Opaque hemithorax in a child: The eyes see what the mind suspects - Ketan Kumar; Joseph L Mathew; Jayashree Muralidharan; Kamal K Singhal; Kushaljit S Sodhi; Pankaj C Vaidya; Meenu Singh (Wolters Kluwer Medknow Publications, 2021)
Background: Children with acute febrile respiratory illnesses are commonly seen in the emergency department. Apart from the initial stabilization, they need to be assessed for the underlying cause, and clinicians should formulate differential diagnoses to start treatment. Radiological investigations including x-ray and ultrasonography are often used to narrow down the initial possibilities based on history and examination. A child presenting with an opaque hemithorax is one such scenario. Clinical Description: A 3-year-old boy presented with a short duration of fever, cough and respiratory distress. Examination showed rightward mediastinal shift with dull percussion note and reduced breath sounds over the left hemithorax, along with congested neck veins, stridor and left sided wheeze. Chest x-ray showed an opacified left hemithorax and ultrasonography suggested moderate pleural effusion. Management: Complicated pneumonia with parapneumonic effusion (or empyema) was considered, but a diagnostic pleural tap was dry. The possibilities were revised to include cystic space occupying lesions with mediastinal compression. Computed tomography of the chest confirmed a mass lesion with predominantly cystic components. The patient underwent surgical excision, and histopathology showed pleuropulmonary blastoma. Conclusion: Although respiratory infections are common in childhood, clinical evaluation and judicious use of imaging modalities can uncover less common conditions. Although bedside ultrasonography is a handy tool in the emergency department, it is not infallible.